2014
DOI: 10.1371/journal.pone.0092355
|View full text |Cite
|
Sign up to set email alerts
|

The Pneumococcal Polysaccharide Capsule and Pneumolysin Differentially Affect CXCL8 and IL-6 Release from Cells of the Upper and Lower Respiratory Tract

Abstract: The polysaccharide capsule and pneumolysin toxin are major virulence factors of the human bacterial pathogen Streptococcus pneumoniae. Colonization of the nasopharynx is asymptomatic but invasion of the lungs can result in invasive pneumonia. Here we show that the capsule suppresses the release of the pro-inflammatory cytokines CXCL8 (IL-8) and IL-6 from the human pharyngeal epithelial cell line Detroit 562. Release of both cytokines was much less from human bronchial epithelial cells (iHBEC) but levels were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“…Antibodies could enhance the ability of neutrophil extracellular traps (NETS) to capture pneumococci [8,9]. Antibodies could counteract the ability of capsule to blunt the release of cytokines such as IL-6 and IL-8 from epithelial cells during the acute phase response [10]. Some non-opsonic, protective, anti-capsular monoclonal antibodies have been shown to decrease IL-8 secretion from leukocytes [11].…”
Section: Multi-modal Protection: Anti-capsular Antibodies Are Not Jusmentioning
confidence: 99%
“…Antibodies could enhance the ability of neutrophil extracellular traps (NETS) to capture pneumococci [8,9]. Antibodies could counteract the ability of capsule to blunt the release of cytokines such as IL-6 and IL-8 from epithelial cells during the acute phase response [10]. Some non-opsonic, protective, anti-capsular monoclonal antibodies have been shown to decrease IL-8 secretion from leukocytes [11].…”
Section: Multi-modal Protection: Anti-capsular Antibodies Are Not Jusmentioning
confidence: 99%
“…Some bacterial pathogens developed mechanisms to control such innate immune inflammatory response to reduce cell infiltration. For example, it has been shown that the presence of CPS of S. pneumoniae down‐regulates the expression of IL‐8/CXCL8 by upper and lower respiratory tract epithelial cells, reducing neutrophil chemotaxis . Although such a role has not been described for S. suis and epithelial cells, significant higher levels of proinflammatory cytokines and chemokines have clearly been observed when endothelial and phagocytic cells have been stimulated with CPS‐negative mutants .…”
Section: How Does Streptococcus Suis Fight Against Early Host Immune mentioning
confidence: 99%
“…This is because the transition from a primary colonization bacterium to a pathogenic bacterium involves a complex interaction between S. pneu-moniae and the body's immune system. There are various components associated with S. pneumoniae-induced immune response, such as the capsule and other virulence factors (5)(6)(7). In addition, many immune cells such as neutrophils, monocytes/macrophages, and dendritic cells are involved in this process (6,(8)(9)(10), which are responsible for the release of factors including IL-1α, IL-1β, IL-6, IFN-α, IL-8, and ICAM-1 (6,8).…”
Section: Introductionmentioning
confidence: 99%